2020
DOI: 10.1007/s10596-020-09996-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the response to geometrical complexity of methods for unstationary simulations in discrete fracture networks with conforming, polygonal, and non-matching grids

Abstract: The aim of this study is to compare numerical methods for the simulation of single-phase flow and transport in fractured media, described here by means of the discrete fracture network (DFN) model. A Darcy problem is solved to compute the advective field, then used in a subsequent time-dependent transport-diffusion-reaction problem. The numerical schemes are benchmarked in terms of flexibility in handling geometrical complexity, mass conservation, and stability issues for advection-dominated flow regimes. To t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…A variable mesh resolution in non-conforming schemes could drastically reduce the number of nodes in the mesh while retaining the the ability to retain higher orders of accuracy. However it is rarely implemented due to the associated meshing complications [10].…”
Section: Discrete Fracture Network: Mesh Generation Backgroundmentioning
confidence: 99%
“…A variable mesh resolution in non-conforming schemes could drastically reduce the number of nodes in the mesh while retaining the the ability to retain higher orders of accuracy. However it is rarely implemented due to the associated meshing complications [10].…”
Section: Discrete Fracture Network: Mesh Generation Backgroundmentioning
confidence: 99%
“…where we recall that Ψ is given in (17) and û := û is as in Lemma 4.2. We can use the direct method of the calculus of variations on E in the Euclidean topology in R. Let (α n ) n∈N ⊂ R be a minimizing sequence for E. Using a similar calculation as in the proof of Theorem 4.7, thanks to (10) we can show that (α n ) n∈N is bounded in R. Therefore, there exists a subsequence of (α n ) n∈N , still denoted by (α n ) n∈N , converging to some α ∈ R. By continuity of Ψ and Fatou's lemma we get that E is lower semi-continuous on R, so that…”
Section: Case λ 1 > λmentioning
confidence: 99%
“…For some specific problems the contribution of the rock matrix is negligible and can be omitted, obtaining the so-called discrete fracture network (DFN) models. On this topic, the reader may refer to [7,10,12,13,17,21,22,28,30] and the references therein. Especially in the presence of complex constitutive equations in the fractures, the authors in [1,2] showed that it is possible to separate the contribution of the porous medium from the fracture network via a Robin-to-Neumann operator.…”
Section: Introductionmentioning
confidence: 99%
“…Using a variable mesh resolution in non-conforming schemes could drastically reduce the number of nodes in the mesh while retaining the the ability to retain a high order of accuracy. However, it is rarely implemented due to the associated meshing complications [8].…”
Section: Discrete Fracture Network and Mesh Generationmentioning
confidence: 99%